A clinical study of the pattern of dermatoses among schoolgoing children attending a tertiary care center in North Karnataka - Umamaheshwari G Chitapur; Sharatchandra B Athanikar; Naveen Narayanshetty Kikkeri; Sweta R Prabhu (Wolters Kluwer Medknow Publications, 2022)
Introduction: Pediatric dermatoses are a distinct group of disorders, comprising skin problems encountered during childhood and adolescence. Objectives of the Study: This study aimed to assess the clinical pattern and prevalence of various dermatoses among schoolgoing children in a tertiary care center in North Karnataka. Materials and Methods: Patients in the age group of 5-14 years with skin diseases attending dermatology outpatient department were enrolled in this study. A predesigned pro forma was used for all cases. A detailed history was taken. Clinical examination and relevant laboratory investigations were done to confirm the diagnosis in doubtful cases. Results: This study included a total of 550 patients. The most common pattern of dermatoses was infections and infestations constituting 40.5% (223 cases). The other common dermatoses in order of prevalence were eczema/dermatitis constituting 14.4% (79 cases), papulosquamous disorders: 6.9% (38 cases), hypersensitivity disorders: 6.2% (34 cases), and pigmentary disorders: 5.1% (28 cases). Among the infections and infestations, fungal infections were most common (14%), followed by parasitic infestations (13.8%), viral infections (8.7%), and bacterial infections (4%). Pityriasis alba was the most common eczematous disease. Conclusion: The most common pattern of dermatoses seen in our study was infections and infestations, followed by eczematous disorders. A detailed knowledge about the pattern of dermatoses among schoolgoing children will help us in implementing essential changes in health education and disease control strategies in the area concerned.